A call to action: informing research and practice in suicide prevention among individuals with psychosis - Chalker, Samantha A.; Sicotte, Roxanne; Bornheimer, Lindsay A.; Parrish, Emma M.; Wastler, Heather; Ehret, Blaire; DeVylder, Jordan; Depp, Colin A. (Frontiers in Psychiatry, 2024)
DeVylder have no COIs. Drs. Chalker and Ehret disclose financial support from CAMS-care (a consulting/training company), and Dr. Chalker discloses financial support from the Zero Suicide Institute. Dr. Depp discloses consulting with Boerhinger-Ingelheim and WCG Clinical.The current manuscript is intended for Frontiers in Psychiatry as it focuses on gaps in the literature relating to the intersection of suicide risk in psychosis and provides clear action steps in how to address these gaps to subsequently improve patient treatment outcomes. This manuscript also best fits with the scope of the Psychopathology section given its focus on improving patient outcomes related to suffering.